Increased Virulence and Large-Scale Reduction in Genome Size of Tetraploid Candida albicans Evolved in Nematode Hosts - Smith, Amanda C.; Rizvi, Hassan; Hickman, Meleah A.; Morran, Levi T. (Frontiers in Fungal Biology, 2022)
Candida albicans is an opportunistic fungal pathogen that causes infections in humans, yet the within-host dynamics of C. albicans infection are not clear. While C. albicans is commonly diploid, it exhibits a range of ploidies, including tetraploidy. Previous work found that tetraploid C. albicans populations exhibited rapid adaptation and significant genome instability when evolved in vitro. Host immune function alters the rate and magnitude of C. albicans virulence evolution, but the effects of the host immunity on tetraploid C. albicans populations are unclear. Here, we tested the effects of the host immunity on genome stability and virulence evolution of tetraploid C. albicans using experimental evolution. We selected for C. albicans increased virulence within either immunocompetent or immunocompromised Caenorhabditis elegans hosts. After nine passages we observed a response to selection for increased virulence. Populations exposed to either immunocompetent or immunocompromised hosts both increased virulence after passage through C. elegans hosts. However, the C. albicans populations passaged through immunocompetent hosts under selection exhibited unique temporal dynamics, a rapid increase in virulence and then subsequent loss of virulence. Most C. albicans populations exhibited genome size reduction within six passages, however populations exposed to immunocompetent hosts exhibited the most rapid transition to ~diploid. Therefore, we found that tetraploids rapidly increase in virulence and decrease genome size within host environments. Further, the combination of selection for greater virulence in the presence of immunocompetent hosts results in major virulence fluctuations and genome size changes. Thus, host immunity significantly impacts the evolutionary trajectories of tetraploid C. albicans.